The Miami-Illinois Digital Archive: Exploring how Linguistic Scholarship can Enlarge our Understanding of the History of Indigenous Societies - Fletcher, Andrew (Cahiers d'histoire)

(untitled) (Cahiers d'histoire, 2019)
Miami-Illinois is an Algonquian language spoken by the Miami and Peoria, whose traditional homelands are situated to the south of the Great Lakes. This area was part of what the French called the Pays d’en Haut. In the 19th century, forced removals and the reservation system led to cultural fragmentation. Language revitalization efforts began in the mid–1990’s and, due to this, a wealth of documentation is now available through the Miami-Illinois Digital Archive. This article shows how this resource can help historians better understand these Indigenous societies.